Evaluating the Differential Impact of Teaching Assistant Training Programs on International Graduate Student Teaching - Meadows, Ken N.; Olsen, Karyn C.; Dimitrov, Nanda; Dawson, Debra L. (Canadian Journal of Higher Education, 2015)
In this study, we compared the effects of a traditional teaching assistant (TA) training program to those of a specialized program, with a substantial intercultural component, for international graduate students. We expected both programs to result in an increase in international graduate students’ teaching self-efficacy, observed teaching effectiveness, and adoption of student-centred approaches to teaching, and we anticipated a greater degree of change for the participants in the specialized program. We found the expected increases for graduate students in both programs, with a larger increase in observed teaching effectiveness for students in the specialized program. We discuss the implications of tailoring TA training programs for international graduate students and of providing time and learning activities for the development of student-centred teaching and reflective practice.